Improving Spiritual Understanding and Mental Health of the Community - Nurhikmah, Nurhikmah; Al Ayyubi, Ibnu Imam; Prayetno, Eko; Hilmansah, Deden; Sholeh, Muh Ibnu; Putra, Ari Limay Trisno (Abdurrauf Journal of Community Service, 2025)
This study aims to assess the effect of enlightening the heart through Friday worship on improving spiritual understanding and mental health of the community in Lempangan Village. This community service programme was carried out by promoting lectures and spiritual coaching focused on the importance of maintaining a clean heart and deepening the meaning of worship. The results showed that participants experienced an increased understanding of the purpose of Friday worship and felt calmer and more peaceful after attending the programme. In addition, the programme was also successful in reducing negative feelings such as stress and anxiety, and strengthening social relationships in the community. Based on these findings, it can be concluded that the enlightenment of the heart through Friday worship has a positive impact on the spirituality and mental well-being of the community, so it can be an effective model to improve the quality of life holistically. Abstrak: Penelitian ini bertujuan untuk mengkaji pengaruh pencerahan hati melalui ibadah Jumat terhadap peningkatan pemahaman spiritual dan kesehatan mental masyarakat di Desa Lempangan. Program pengabdian kepada masyarakat ini dilaksanakan dengan mengedepankan ceramah dan pembinaan spiritual yang difokuskan pada pentingnya menjaga kebersihan hati dan pendalaman makna ibadah. Hasil penelitian menunjukkan bahwa peserta mengalami peningkatan pemahaman tentang tujuan ibadah Jumat dan merasa lebih tenang dan damai setelah mengikuti program tersebut. Selain itu, program ini juga berhasil mengurangi perasaan negatif seperti stres dan cemas, serta mempererat hubungan sosial di masyarakat. Berdasarkan temuan tersebut, dapat disimpulkan bahwa pencerahan hati melalui ibadah Jumat berdampak positif terhadap spiritualitas dan kesejahteraan mental masyarakat, sehingga dapat menjadi model yang efektif untuk meningkatkan kualitas hidup secara holistik. Keywords: Pencerahan Qalbu, Ibadah Jumat, Spiritualitas, Kesehatan Mental Kata Kunci: Pencerahan Qalbu, Ibadah Jumat, Spiritualitas, Kesehatan Mental